Testicular infiltration due to acute lymphoblastic leukemia presented as a testicular mass: A case report - Herrera-Lomonaco, Sandra (2017)
Acute lymphoblastic leukemia is a common pediatric neoplasia, comprising 11% of all leukemias. In Colombia, the annual incidence in adults is 1 out of 100,000 people. Testicular relapse is rare (accounting for only 0.9-8.8% of all cases) and represents a sign of recurrence which can be confused with other testicular conditions. We report the case of a 23-yearold male with testicular pain and swelling for 2 months after a trauma, and a history of acute lymphoblastic leukemia treated 4 years before. A testicular ultrasound suggested tension hydrocele. The patient was taken to surgery where a testis with neoplastic features was observed. Therefore, an orchiectomy was performed. The pathological anatomy revealed a 12-cm mass consisting of infiltration by leukemic cells, showing a positive expression for CD19, CD10, and a negative expression for TdT. The testes are considered a sanctuary site for leukemic cells. However, the formation of a mass that mimic a testicular tumor may exceptionally be observed.